Pengolahan Sampah Organik Bank Sampah Pematang Pudu Bersih Kecamatan Mandau Kabupaten Bengkalis - Prama Widayat; Ryan Pahlawan (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
Mandau District is one of the most densely populated districts in Bengkalis Regency, here there is a Pematang Pudu Clean Waste Bank located in Pematang Pudu village with a population of 29,986 people consisting of 17 RW and 95 RT with an area of 25 Km2. This waste bank was established in 2015 which accommodates non-organic waste such as bottles, plastic, paper and cardboard of various types. In addition, there is also organic waste such as leaves, fruit peels from traders around Pematang Pudu Village, but this has not been optimally processed due to limited capabilities and human resources. Even though the potential is quite large to encourage an increase in the income of the waste bank apart from non-organic waste. Therefore, organic waste processing is carried out with 2 models, namely using a starter or composter EM4 and M21, from these two processes it turns out to produce compost at the same time, neither is faster, which both take 30 calendar days.